2010
DOI: 10.1136/gut.2010.233023
|View full text |Cite
|
Sign up to set email alerts
|

Limited effect of summer warming on the sensitivity of colorectal cancer screening: Table 1

Abstract: In their recent paper, Grazzini and colleagues 1 reported a decrease in the positivity of the immunochemical faecal occult blood test (iFOBT) for colorectal cancer screening during the summer period. Their results predict a higher rate of false-negative iFOBT results during the hot season. This effect is likely to be higher for patients with minor neoplastic lesions, where the haemoglobin concentration in faeces is usually lower 2 than in patients with larger adenomas or invasive cancers.Evaluating the seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Sensitivities and specificities were examined at five different FIT cutoffs using the same FIT and the same buffer solution. Actual temperatures for each day from sampling until the beginning of the cold chain were used rather than monthly 9 , 10 or seasonal 6 averages. Our study is, to our knowledge, the first to investigate the potential influence of both temperature and sample return time on sensitivity and specificity of FIT for several cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivities and specificities were examined at five different FIT cutoffs using the same FIT and the same buffer solution. Actual temperatures for each day from sampling until the beginning of the cold chain were used rather than monthly 9 , 10 or seasonal 6 averages. Our study is, to our knowledge, the first to investigate the potential influence of both temperature and sample return time on sensitivity and specificity of FIT for several cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Our study could not evaluate the seasonal variation of proportional incidence, however, the impact of warming on the frequency of interval cancers has been shown to be limited. 34 Moreover, some manufacturers of FIT recently modified the buffer of their products to prevent haemoglobin degradation at high temperatures. 35…”
Section: Discussionmentioning
confidence: 99%
“…Grazzini and colleagues 8 suggest that the differences between the two studies could be attributed to the significantly lower average temperature in the Netherlands, and that the relationship between ambient temperature and the degradation of the globin might have a non-linear relationship, with manifest effects even at low temperatures. Zorzi and colleagues 9 in a study of five screening centres in Italy found a higher incidence of interval cancers after tests that had been carried out in the summer compared with those performed in the winter. We investigated the influence of ambient temperature on the main early-impact indicators in the screening programme of Emilia-Romagna, a populous region of northern Italy (4,471,104 residents in 2012) with a sub-continental climate, significant annual temperature ranges, hot summers, and severe winters.…”
Section: Introductionmentioning
confidence: 97%